2023
DOI: 10.21203/rs.3.rs-2963790/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct regulation of the cardiac ryanodine receptor (RyR2) by O-GlcNAcylation

Abstract: Background O-GlcNAcylation is the enzymatic addition of a sugar, O-linked β-N-Acetylglucosamine, to the serine and threonine residues of proteins, and is abundant in diabetic conditions. We have previously shown that O-GlcNAcylation can trigger arrhythmias by indirectly increasing pathological Ca2+ leak through the cardiac ryanodine receptor (RyR2) via Ca2+/calmodulin-dependent kinase II (CaMKII). However, RyR2 is well known to be directly regulated by other forms of serine and threonine modification, therefo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The study of regional integration in the third world has indicated that little success has been achieved largely due to limited authority of their institutional structures. Okolo pointed out that in most cases member-states retain the right to veto legislations approved by their representatives at the regional level (Okolo, 2015). Nye has also argued that strong extraregional actors have played a tremendous role to either promote or hamper progress towards integration in the third world countries (Nye, 2011), since it is a truism that third world countries are highly dependent upon industrialized states for development capital, markets for raw materials and technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study of regional integration in the third world has indicated that little success has been achieved largely due to limited authority of their institutional structures. Okolo pointed out that in most cases member-states retain the right to veto legislations approved by their representatives at the regional level (Okolo, 2015). Nye has also argued that strong extraregional actors have played a tremendous role to either promote or hamper progress towards integration in the third world countries (Nye, 2011), since it is a truism that third world countries are highly dependent upon industrialized states for development capital, markets for raw materials and technology.…”
Section: Literature Reviewmentioning
confidence: 99%